AKSELERASI MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR MELALUI PEMANFAATAN MEDIA MANIPULATIF BLOCK DIENES - Veronica Yonita Wongkar; Stief Aristo Walewangko; Agustina Regina Banua; Ignatius Rolly Cun Rorah (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The primary issue examined in this study concentrates on the inadequate levels of motivation and defective learning outcomes in mathematics, particularly with regard to place value, among third-grade students at SD Negeri 72 Manado. The acceleration of student motivation and learning outcomes was achieved through modifications to instructional practices, including the use of block dienes media, and the implementation of specific and practical classroom management strategies. The subjects of this study were 24 third-grade students.The present study was conceived as a classroom-based action research project, which comprised two cycles of planning, action, observation, and reflection. The data presented herein were collected via a series of empirical methods, including tests, observations, interviews, documentation, and a learning motivation questionnaire. The findings of the study suggest that the utilisation of Dienes blocks as a medium for instruction can enhance students' motivation and academic performance in the domain of mathematics. With regard to the learning outcomes, the results of the students' pre-cycle tests demonstrated that a mere two out of 24 students met the proficiency standards, resulting in a proficiency rate of 8.33%. In Cycle I, the results of the assessments indicated that 8 out of 24 students demonstrated proficiency, with a proficiency rate of 33.33%. The number of students who met the proficiency criteria in Cycle II increased to 21 students, with a proficiency rate of 87%. Furthermore, an enhancement in students' learning motivation was also observed. In Cycle I, the mean score for learning motivation was 61.66%, with all motivation indicators falling within the "moderate" category. In Cycle II, the students' learning motivation score reached 93.28%, meeting the "very high" criterion. It has been demonstrated that the utilisation of Dienes blocks as a medium for manipulation has been shown to enhance the motivation and learning outcomes of third-grade students at SD Negeri 72 Manado. It is recommended that teachers utilise Dienes blocks in mathematics instruction at the elementary school level. ABSTRAK Masalah utama penelitian ini adalah rendahnya motivasi dan hasil belajar matematika khususnya materi nilai tempat, siswa kelas 3 SD Negeri 72 Manado. Penelitian ini bertujuan untuk mengakselerasi motivasi dan hasil belajar matematika siswa melalui pemanfaatan media manipulatif block dienes serta penanganan kelas secara spesifik dan nyata. Subjek penelitian ini adalah 24 siswa kelas 3. Penelitian ini disusun menurut skema penelitian tindakan kelas dalam 2 siklus yang terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data penelitian dikumpulkan melalui tes, observasi, wawancara, dokumentasi dan pengisian angket motivasi belajar. Hasil penelitian menunjukkan bahwa penggunaan media manipulatif block dienes dapat meningkatkan motivasi dan hasil belajar matematika siswa. Pada area hasil belajar, hasil tes prasiklus siswa menunjukkan bahwa hanya terdapat 2 dari 24 siswa yang tuntas, dengan persentase ketuntasan sebesar 8,33%. Pada siklus I, hasil tes menunjukkan terdapat 8 dari 24 siswa dinyatakan tuntas dengan persentase ketuntasan mencapai 33,33%. Jumlah siswa tuntas pada siklus II meningkat menjadi 21 siswa dengan persentase ketuntasan 87%. Peningkatan juga terlihat pada motivasi belajar siswa. Motivasi belajar siklus 1 memperoleh skor sebesar 61,66%, dengan semua indikator motivasi termasuk dalam kriteria ‘sedang’. Pada siklus II, skor motivasi belajar siswa mencapai 93,28%, dengan kriteria ‘sangat tinggi’. Dengan demikian, pemanfaatan media manipulatif block dienes terbukti secara efektif dapat meningkatkan motivasi dan hasil belajar siswa kelas 3 SD Negeri 72 Manado. Disarankan kepada guru agar menggunakan media block dienes dalam pembelajaran matematika di Sekolah Dasar.